Artery of Percheron Infarction as an Unusual Cause of Korsakoff’s Syndrome - Yongxing Zhou; Derrick Fox; Abhishek Anand; Amal Elhaj; Arushi Kapoor; Faranak Najibi; Han Kim; Roger Weir; Annapurni Jayam-Trouth (Case Reports in Neurological Medicine)
The Korsakoff syndrome is defined as “an abnormal mental state in which memory and learning are affected out of all proportion to other cognitive functions in an otherwise alert and responsive patient.” Confabulation refers to false or erroneous memories arising, not deliberately, in the context of a neurological amnesia and is often thought of as pathognomonic of the Korsakoff syndrome. Although the exact pathophysiology is unknown, various studies have identified brain lesions in the thalami, mammillary bodies, and frontal cortex. We report a case of a 68-year-old male presenting with acute altered mental status on July 16, 2015. The neuropsychological dysfunctions included prominent Korsakoff’s syndrome, which became apparent when the altered mental status resolved. Amnesia was accompanied by prominent confabulation, disorientation, and lack of insight into his own disability. Neuroradiological data indicated that the intralaminar and dorsomedial nuclei in bilateral thalami were infarcted by occlusion of the artery of Percheron. We believe that ours is one of few reported cases of Korsakoff syndrome in a patient with infarction involving the territory of the artery of Percheron. We conclude that bilateral thalamic lesions could cause Korsakoff’s syndrome and the intralaminar and dorsomedial nuclei might be important structures in the pathogenesis of confabulation.